Potential impacts of climate change on biodiversity : in Central America, Mexico, and the Dominican Republic - Anderson, Eric; Cherrington, Emil A.; Flores, Africa; Perez, Joel; Sempris, Emilio (CATHALAC, 2021)
This study is an effort to better understand how climate change might affect the biological resources our region possesses. In addition to the important scientific findings presented here, this study presents an undeniable opportunity for action, to begin taking the steps to reverse adverse trends. It is our sincere hope that the results of this study are incorporated in the respective National reports to the UNFCCC and the CBD whose preparation is underway.